2011
DOI: 10.4244/eijv7ska15
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-eluting balloon angioplasty and cobalt-chromium stents versus conventional angioplasty and paclitaxel-eluting stents in the treatment of native coronary artery stenoses in patients with diabetes mellitus

Abstract: The clinical and angiographic outcome of the combination of the drug-eluting balloon SeQuent Please with a cobalt chromium stent compared to the drug eluting Taxus stent are similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…Studies recruited from different patient populations. In the trial by Ali and colleagues (31), all patients were diabetic; whereas, in trials conducted by Besic et al (23) and Poerner et al (25) all patients were hypertensive. Data for each trial are detailed in Table 2.…”
Section: Characteristics Of the Patients And Study Designsmentioning
confidence: 83%
See 1 more Smart Citation
“…Studies recruited from different patient populations. In the trial by Ali and colleagues (31), all patients were diabetic; whereas, in trials conducted by Besic et al (23) and Poerner et al (25) all patients were hypertensive. Data for each trial are detailed in Table 2.…”
Section: Characteristics Of the Patients And Study Designsmentioning
confidence: 83%
“…Following screening for replicates, 405 remained; and after screening abstracts for relevance, a further 371 studies were removed. Finally, full text of the remaining 34 studies were screened, of which 17 randomised controlled trials (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) fulfilled the inclusion criteria and were qualitatively and quantitatively analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown inconsistent results regarding the antiproliferative strength of such an adjunctive procedure [5][6][7][8][9][10]. Yet, no data about the time course of arterial vessel response and stent coverage after such a procedure is available.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, we cannot anticipate whether the greater, but diffuse proliferation in the DEB stent group possibly translate into a relevant in-stent restenoses at a later stage. In a study from Ali et al, 11 comparing DEB+BMS versus DEB, significant differences for binary restenosis, major adverse cardiovascular events, or revascularization procedures after 9 months were also not observed. Previously reported data of neointimal proliferation after a DEB stent procedure is similar to ours (relative proliferation volume: 26.1% in this trial versus 25.1% in Gutiérrez-Chico et al).…”
Section: Proliferationmentioning
confidence: 99%
“…[5][6][7][8][9] To date, there is limited knowledge on the combination of bare metal stent (BMS) postdilated with a drug-eluting balloon. [10][11][12] Optical coherence tomography (OCT) is a new gold standard in intravascular imaging allowing the assessment of detailed vessel and stent structures with an axial resolution of 10 to 20 μm. Evolved algorithms to evaluate 2-and 3-dimensional proliferation parameters with OCT are of crucial importance to gain additional benefit compared with standard quantitative coronary angiography but are often deficient in reported OCT studies.…”
mentioning
confidence: 99%